Foundations in microbiology W/bound in olc card - Talaro, Kathleen Park. ([S.l.] : McGraw-Hill Science/Engineering/Math, 2004)
Written with the non-major/allied health student in mind, the authors use common, everyday analogies to explain the many difficult microbiology concepts. Unlike any other allied health microbiology textbook on the market, the art program showcases beautiful illustrations with the use of bold, primary colors. A taxonomic approach is used for the study of pathogens.
Keywords: microbiology,biology